Environmental Social Governance Characteristics Impact on Inward Foreign Direct Investment - Muhammad Ubaidillah Al Mustofa; Imron Mawardi; Raditya Sukmana; Puput Rosita Febrianti (Airlangga Journal of Innovation Management, 2026)
This study aims to examine the influence of Environmental, Social, and Governance (ESG) characteristics and selected macroeconomic factors on inward foreign direct investment (FDI) in member states of the Organization of Islamic Cooperation (OIC). Using panel regression analysis, this study investigates 50 OIC countries over the period 2002–2019. The findings reveal that the aggregate ESG index does not significantly influence inward FDI. However, when ESG is examined separately, the Environmental dimension has a significant effect, indicating that environmental conditions are considered by foreign investors in making investment decisions. In contrast, the Social and Governance dimensions do not significantly affect inward FDI. The results also show that inflation has a positive and consistent effect on inward FDI, suggesting that foreign investors may interpret inflation as a signal of market activity and economic expansion. Meanwhile, the MENA region has a negative effect on inward FDI, reflecting investor concerns regarding political instability, regulatory uncertainty, and regional risk. The research implication of this study is that ESG should not always be treated as a single composite measure, as each ESG dimension may influence investment decisions differently. From a managerial and policy perspective, OIC governments should strengthen environmental quality, maintain macroeconomic stability, reduce regional political risk, and improve institutional credibility to attract sustainable foreign investment. This study contributes to the ESG–FDI literature by providing evidence from OIC economies.